Utilization of Google From as a Quiz for Learning Fiqh - Reilly Saskia; Murota Okuda; Brink Cooney (Scientechno: Journal of Science and Technology, 2023)
As users of technology, humans must be able to use it in the present and future. Therefore, educational institutions, especially schools, can use this technological development to support teaching and learning. One of them is using Google Forms (Google Forms) as a quiz for fiqh learning. This study aims to improve student learning outcomes and discover the benefits of Google Forms as a quiz in fiqh learning. This research method uses quantitative methods using survey models and in-depth interviews. The survey used in this research is online-based. The results of this study indicate that students' understanding increases when educators use this Google form as a quiz for Fiqh learning in schools. The conclusion of this study explains that using the Google form is beneficial for educators in teaching and learning science subjects and awakens students' enthusiasm for learning so that student achievement increases. Therefore, the limitation of this study is that the researcher only researched the use of the Google form as a quiz for fiqh learning. The researcher hopes that further researchers can conduct research on using the Google form as a quiz and develop it in other subjects.